Performing DIY Museums in Murihiku: Decentralising the Museum - McCully, Kathryn (Auckland University of Technology, 2020)
DIY Museums explore a decentralised museum model, that regards the city and region as the site for responsive, intermittent acts of museum-making performed by and through the community. Part physical, portable and virtual, DIY Museums evolved in response to the arts and cultural environment in Mirihiku (Southland), Nui Tireni (New Zealand), where the candidate lives and works. Over the past nine years, this community has seen the decline of its arts and cultural institutions, including the closure of Southland Museum and Art Gallery, Southland Art Society’s City Gallery and Anderson Park Art Gallery. In this environment, the DIY Museums research explores a proliferation of ‘small’ and ‘micro’ museums, positioning their practices as unique and authentic DIY modalities that are marginalised in favour of homogenised definitions and codes of museum professionalism. With ‘small’ and ‘micro’ museums making up ninety percent of the sector in Nui Tireni, Murihiku is home to over forty museums, most defined as ‘micro’ or having no permanent full-time staff. The DIY Museums re-imagine authority and value, through practice, occupying positions of ‘in-betweenness’ and challenging frameworks that have historically colonised bodies of knowledge. The exegesis argues that differentiating communities as ‘amateurs’, in the expression of their own unique bodies of knowledge, characterises how an adherence to rigid codes of professionalism creates ruptures or ‘disremption’ (Digger, 1994) between communities and their museums. The compositing of discontinuous still and animated frames as ‘fragments and moments’ (Crang, 2003) documents museum-making in Murihiku as a way to preserve DIY modalities of practice and reveal museum ‘fictions’ in the performance of ‘professionalism as a self-promoted quality’ (McCredie, 1999). The candidate’s role as a socially-engaged artist and curator in DIY Museums reflects her extensive cross-disciplinary experience in ‘small’ and ‘micro’ museums; at times curator, administrator, artist, collections manager, chairperson and so on. The DIY Museums project serves as a field-test that sets the stage for the facilitation of a new conception of museum professionalism consistent with socially-engaged art practice and institutional critique.
Keywords: DIY; Museums; Socialy-engaged art practice; Regional